Effect of a multi-component, participatory social and health promoting intervention on health and wellbeing in refugee families from Syria resettled in Denmark - Nina Odgaard Nielsen; Anne Vollen Rafn; Signe Andersen; Jan Rafn; Hanne Kjærsgaard; Birthe Petersen; Anne Juul Sønderskov; Morten Dahl; Eirikur Benedikz; Marianne Lindahl (Journal of Migration and Health)
Aim: The aim was to evaluate the effect of a multi-component social and health promoting intervention on health and wellbeing in a well-defined group of refugee families 2–4 years after resettlement in Denmark. Methods: This longitudinal open-label comparison study involved 82 individuals from Syria aged 13–53 years comprising an intervention group (IG, n = 50) and a comparison group (CG, n = 32), was conducted from 2019 to 2021. The main outcomes were self-rated health, assessed using a single item question from the Danish National Health Surveys, and mental wellbeing measured by the Short Warwick-Edinburgh Mental Wellbeing Scale (SWEMWBS). Objective levels of cholesterol, blood glucose (HbA1c), and blood pressure were also determined. Multiple linear regression models were used to estimate the effect of the intervention on SWEMWBS scores. Results: A higher proportion in the IG (38 %) than in the CG (22 %) had rated their general health more positively after the intervention, though the difference was statistically insignificant (p = 0.38). There was a less decrease in SWEMWBS scores in the IG (slope 0.47) than in the CG (slope 0.27) from 2019 to 2020, indicating a positive, but insignificant, effect of the intervention (estimate: 0.20, 95 % CI:0.06 – 0.47, p = 0.13). This tendency of a positive effect was absent in 2021. High participation rate was significantly associated with higher post-intervention SWEMWBS scores (coefficient: 3.45, 95 % CI: 1.86 – 5.03, p < 0.01). No effects on objectively measured biomarkers were observed. Conclusions: The study demonstrated changes in self-rated health and SWEMWBS scores in the IG and CG, and indicated an overall tendency of a positive effect of the intervention on general health and mental wellbeing among the study participants. The effects might have been more pronounced without the convergence of counteracting factors, such as the COVID-19 pandemic and substantial fear arising from the European repatriation policies debated in 2021.